2005
DOI: 10.1183/18106838.0201.50
|View full text |Cite
|
Sign up to set email alerts
|

Induced sputum in occupational lung diseases

Abstract: Key pointsBAL, an important tool in assessing occupational lung diseases, is an invasive technique and thus unsuitable for screening programmes, the evaluation of exposure and the monitoring of hazardous dust.Examination of induced sputum is a noninvasive method to directly study particulate burden and inflammatory processes in the lung.The correlation between cells retrieved by BAL and induced sputum shows different proportions of leukocytes, but similar eosinophil cell counts and qualitative/quantitative ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
6
1
2
Order By: Relevance
“…In contrast with the findings of previous studies, (18) the current results did not reveal any differences in the CD4/CD8 ratio between the study groups in showing that a high variability in CD4/CD8 T lymphocyte may be present in CBD, as in sarcoidosis. (28) Although the change in CD4/CD8 ratio was also not significant after follow-up, a clear accumulation of CD4 T lymphocytes in IS samples was observed over time for all individuals tested.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with the findings of previous studies, (18) the current results did not reveal any differences in the CD4/CD8 ratio between the study groups in showing that a high variability in CD4/CD8 T lymphocyte may be present in CBD, as in sarcoidosis. (28) Although the change in CD4/CD8 ratio was also not significant after follow-up, a clear accumulation of CD4 T lymphocytes in IS samples was observed over time for all individuals tested.…”
Section: Discussioncontrasting
confidence: 99%
“…By virtue of it being a safe and simple procedure, induced sputum was investigated for its ability to assess occupational exposures [32 ]. Several investigators showed the relevance of asbestos bodies present in spontaneous sputum compared with BAL.…”
Section: Induced Sputum In Occupational Lung Diseasesmentioning
confidence: 99%
“…Such pathophysiological processes can be identified by means of a wide range of diagnostic tools, which still represent the gold standard in epidemiological and clinical settings, including bronchoscopy or bronchoalveolar lavage (BAL), or less invasive induced sputum, to sample particulate burden and assess the involvement of inflammatory and structural cells. However, they cannot be extensively applied in routine clinical practice because of their relative invasiveness, which hampers their use in screening programs, exposure monitoring or the follow-up of workers exposed to hazardous pollutants [2].…”
Section: Introductionmentioning
confidence: 99%